Działalność duszpasterska ks. dr. Grzegorza Okroya TChr (Colloquia Theologica Ottoniana, 2013)
Society of Christ, dr Grzegorz Okroy was the founder of Academic Ministry in the parish of the Sacred Heart of Jesus, which very quickly became the most energetic centre of its kind in Szczecin. This article is devoted to the pastoral activity period for Szczecin of priest Okroy which yielded cooperation and friendships, even after leaving this city. The fi gure shown is the pastor of the various parties in the relationship and co dependents, in the record in the annals of the parish and the Academic Ministry, in his own memoirs, as well as statements and reports Communist State Security Service. Priest Grzegorz Okroy, the students called him “Delo”, was the pastor demanding, but also caring. He took care of the spiritual and intellectual development of their charges. After his departure from Szczecin, including for scientifi c work and ministry among the Polish immigrants of German, not leave them, but he continued to work responsibly and sustain old bonds. Many of them survived, including through annual meetings and passed from hand to hand letters to his death